Advanced distributed architecture for a complex and large scale Arabic handwriting recognition framework. (2017) - Hassen, Hamdi; Dörnemann, Kay; Khemakhem, Maher
Several Arabic handwritten recognition systems (AHRS) have been widely used since the early nineties, proposing high recognition rates, but limited to small and medium document quantity. Indeed, a variety of approaches, methods, algorithms and techniques have been proposed to build a powerful AHRS able to recognise and digitise such documents. Unfortunately, these methods cannot succeed to achieve this mission for large amounts of documents. Distributed computing architectures such as clusters, grid computing, peer to peer and cloud computing provide enough computing power and/or data storage capacities. This paper describes the design and implementation of a large AHRS solution based on distributed computing architectures. The experiments were conducted on real grid computing environment, a peer-to-peer scheduling architecture and the Amazon Elastic Compute Cloud, with a real large scaled dataset from the IFN/ENIT database. Experimental results confirm indeed that distributed computing environments constitute adequate infrastructures for building fast and powerful AHRS.